Src activation decouples cell division orientation from cell geometry in mammalian cells. (July 2018) - Sun, Xiaoyan; Qi, Hongsheng; Zhang, Xiuzhen; Li, Li; Zhang, Jiaping; Zeng, Qunli; Laszlo, George S.; Wei, Bo; Li, Tianhong; Jiang, Jianxin; Mogilner, Alex; Fu, Xiaobing; et al.
Abstract: Orientation of cell division plane plays a crucial role in morphogenesis and regeneration. Misoriented cell division underlies many important diseases, such as cancer. Studies with Drosophila and C. elegance models show that Src, a proto-oncogene tyrosine-protein kinase, is a critical regulator of this aspect of mitosis. However, the role for Src in controlling cell division orientation in mammalian cells is not well understood. Using genetic and pharmacological approaches and two extracellular signals to orient cell division, we demonstrated a critical role for Src. Either knockout or pharmacological inhibition of Src would retain the fidelity of cell division orientation with the long-axis orientation of mother cells. Conversely, re-expression of Src would decouple cell division orientation from the pre-division orientation of the long axis of mother cells. Cell division orientation in human breast and gastric cancer tissues showed that the Src activation level correlated with the degree of mitotic spindle misorientation relative to the apical surface. Examination of proteins associated with cortical actin revealed that Src activation regulated the accumulation and local density of adhesion proteins on the sites of cell-matrix attachment. By analyzing division patterns in the cells with or without Src activation and through use of a mathematical model, we further support our findings and provide evidence for a previously unknown role for Src in regulating cell division orientation in relation to the pre-division geometry of mother cells, which may contribute to the misoriented cell division.